TI_GERICHTE 52.2017.459 vom 5. Juli 2017 , Licenza edilizia a posteriori per un manufatto per la copertura di due posteggi - TI Tribunale d'appello (2017)
Licenza edilizia a posteriori per un manufatto per la copertura di due posteggi